Two Cases of Statin-Induced Immune-Mediated Necrotizing Myopathy: A Rare Side Effect of Statins - Luis Angel Montero Furelos; Clara Fernandez Peña; Beatriz San Millan Tejedor (Rheumato)
Statins are effective drugs for lowering cholesterol and reducing cardiovascular risk. Rarely, they can trigger autoimmune myopathies like immune-mediated necrotizing myopathy (IMNM), associated with anti-HMGCR antibodies. This condition may persist after statin discontinuation and requires immunosuppressive treatment. Despite these rare side effects, the benefits of statins outweigh the risks for most patients.